2016
DOI: 10.1007/s00330-016-4691-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric computer-aided differential diagnosis of Alzheimer’s disease and frontotemporal dementia using structural and advanced MRI

Abstract: ObjectivesTo investigate the added diagnostic value of arterial spin labelling (ASL) and diffusion tensor imaging (DTI) to structural MRI for computer-aided classification of Alzheimer's disease (AD), frontotemporal dementia (FTD), and controls.MethodsThis retrospective study used MRI data from 24 early-onset AD and 33 early-onset FTD patients and 34 controls (CN). Classification was based on voxel-wise feature maps derived from structural MRI, ASL, and DTI. Support vector machines (SVMs) were trained to class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
82
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 43 publications
4
82
1
Order By: Relevance
“…We speculate that other algorithms that utilize more sophisticated feature combination approaches, like sparse group lasso models [61], or hierarchical or longitudinal algorithms that aim to differentiate patients from a general population in order to subsequently differentiate between dementia-types may further exploit and weigh the additional information from multiple measures [64]. Incorporating other or additional imaging-derived biomarkers as cerebral blood flow [65], amplitude of low frequency fluctuations [32], GM derived connectomics [19], or diffusion tractography derived graph-based analytics [61] may further contribute to MRI-based dementiatype classification estimates without increasing diagnostic complexity.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that other algorithms that utilize more sophisticated feature combination approaches, like sparse group lasso models [61], or hierarchical or longitudinal algorithms that aim to differentiate patients from a general population in order to subsequently differentiate between dementia-types may further exploit and weigh the additional information from multiple measures [64]. Incorporating other or additional imaging-derived biomarkers as cerebral blood flow [65], amplitude of low frequency fluctuations [32], GM derived connectomics [19], or diffusion tractography derived graph-based analytics [61] may further contribute to MRI-based dementiatype classification estimates without increasing diagnostic complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous MRI‐based classification methods have been heralded as promising tools for accurate classification of AD (Bouts et al, ; Bron et al, ; Schouten et al, ), MCI (Cui et al, ; Eskildsen et al, ), or to differentiate between MCI subjects likely to develop dementia due to AD or those that do not progress (Adaszewski et al, ; Arbabshirani, Plis, Sui, & Calhoun, ; Eskildsen et al, ; Misra et al, ; Rathore et al, ). These studies generally aimed to maximize classification performance by using sparse, carefully selected clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…While the other models used a separate clinical cohort for training. Nevertheless, it was previously observed that MCI detection models that used DTI‐derived measures (Dyrba et al, ) or combinations with measures of GM atrophy were best for the detection of MCI (Cui et al, ; Fan et al, ) or AD (Bron et al, ; Rathore et al, ; Schouten et al, ). We also found that only those models that either used DTI‐derived measures of impaired WM integrity or combined these with measures of GM atrophy were better than chance for MCI detection within the RS cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations